Clinical methods of neuro-ophthalmologic examination - Kestenbaum, Alfred, 1890-1961 (William Heinemann, 1947)
Clinical Methods of Neuro-Ophthalmologic Examination presents the clinical methods of ophthalmologic examination that may be helpful in neurologic differential diagnosis. Neuro-ophthalmologic examination has developed in two directions: the more precise methods and the unrefined yet fairly exact methods, such as diagnostic measurement by means of a simple ruler. This book is based on lectures delivered by the author to neurologists and ophthalmologists. This book is composed of 13 chapters and begins with a presentation of anatomic details that are important for the understanding of the variou.